2008
DOI: 10.1007/978-3-540-88737-9_3
|View full text |Cite
|
Sign up to set email alerts
|

On Combining Description Logic Ontologies and Nonrecursive Datalog Rules

Abstract: Abstract. Reasoning in systems integrating Description Logics (DL) ontologies and Datalog rules is a very hard task, and previous studies have shown undecidability of reasoning in systems integrating (even very simple) DL ontologies with recursive Datalog. However, the results obtained so far constitute a very partial picture of the computational properties of systems combining DL ontologies and Datalog rules. The aim of this paper is to contribute to complete this picture, extending the computational analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…This is mainly due to undecidability of reasoning in such systems. This is particularly the case for those systems integrating DL ontologies with recursive or hybrid rules [57,58]. So, bridging the discrepancy in these two knowledge representations is a challenging problem.…”
Section: Ontology Reasoningmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly due to undecidability of reasoning in such systems. This is particularly the case for those systems integrating DL ontologies with recursive or hybrid rules [57,58]. So, bridging the discrepancy in these two knowledge representations is a challenging problem.…”
Section: Ontology Reasoningmentioning
confidence: 99%
“…So, bridging the discrepancy in these two knowledge representations is a challenging problem. Many studies [57][58][59][60] have shown that to avoid undecidability of reasoning, practically all decidable approaches to integrating ontologies and rules should impose specific conditions which restrict the interaction between the rules and the ontology. In this work, we adopt a similar decidable reasoning approach by adhering to restrictions, such as avoiding recursive and hybrid rules.…”
Section: Ontology Reasoningmentioning
confidence: 99%
“…Additionally, there might be other predicate symbols available, but without loss of generality we assume they cannot coincide with complex concept or role descriptions. Note that we do not impose Datalog safeness or (weakly) DL safeness [28,30,29] for the rule component. Intuitively, the restricted shape of FoLPs suffices to guarantee decidability; FoLPs are in general neither Datalog safe nor weakly DL-safe; we will discuss the relation with weakly DL-safeness in detail in Section 6.…”
Section: Definition 52mentioning
confidence: 99%
“…Furthermore, they serve well as an underlying integration vehicle for ontologies and rules. In order to illustrate this, we define f-hybrid knowledge bases (fKBs), consisting of a SHOQ knowledge base and a rule component that is a FoLP, with a nonmonotonic semantics similar to the semantics of g-hybrid knowledge bases [12], r-hybrid knowledge bases [30], and DL+log [29]. Our approach differs in two points with current other proposals:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation